Epidemiological profile of breast cancer in a reference center in the north region of Brazil - Daniele Carvalhais França; Agnaldo Lopes da Silva Filho; Anisse Marques Chami; Leticia da Conceição Braga (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: To describe the epidemiological data of women with breast cancer at a referral center in oncology in the northern region of Brazil. Methods: This is a retrospective cohort study. The study population consists of patients who were diagnosed with in situ or invasive BC (invasive carcinoma of no special type (ICNST) and invasive lobular carcinoma (ILC)) at the Hospital de Amor da Amazônia, in Porto Velho – Rondônia, between January 2012 and December 2021. The sampling plan adopted was of the convenience type. All patients who received the anatomopathological diagnosis of in situ or invasive BC at the Hospital de Amor da Amazônia from 2012 to 2021 and came from the North region were included. Exclusion criteria were non-origin from the North region and absence of diagnosis established by anatomopathological examination of breast cancer. Analysis of the database and medical records of the Hospital de Amor da Amazônia was carried out to collect information. Results: 420 patients were included, 99.5% female, with complete elementary school (32,6%) and brown skin (68,1%). The mean age at diagnosis was 49 years. Forty-five percent were born in the northern region and 55% in other regions of Brazil. Eighty percent of tumors were invasive ductal carcinoma; 32.7% were luminal A-like, 25.1% luminal B-like, 19.4% HER2 enriched and 12.8% triple negative. When patients were subdivided by age ≤40 years and > 40 years, there was a statistically significant difference in the association with staging (p=0.000), histological type (p= 0.035), immunohistochemistry subtype (p=0.000), neoadjuvant chemotherapy (p=.000) and genetic counseling (p=0.001). The median survival was 7.99 years. The 5-year overall survival was 81%. The higher the stage, the lower the survival rate. Twenty-four distinct variants were described in patients undergoing genetic testing, 16 of uncertain significance and 8 pathogenic. Three new variants were described: ATM (c.8726G>C), BRCA2 (c.2232A>C) and ERCC5 (c.2164G>Ap). Conclusion: In this study, the age at diagnosis of breast cancer was lower, the tumor subtype was more aggressive, and patients were admitted in more advanced stages. Overall survival is lower compared to national and international data. Despite the small number of patients referred to genetic testing, it is important to search for germline mutations to improve patients’ diagnosis and treatment.